Answer:
Step-by-step explanation:
Check attachment for solution
Answer:
x = 3
Step-by-step explanation:
Given
- 3x + 2 = - 7 ( subtract 2 from both sides )
- 3x = - 9 ( divide both sides by - 3 )
x = 3
Step-by-step explanation:
![27 \times \frac{1}{ {3}^{3} }](https://tex.z-dn.net/?f=27%20%5Ctimes%20%20%5Cfrac%7B1%7D%7B%20%7B3%7D%5E%7B3%7D%20%7D%20)
![= 27 \times \frac{1}{27}](https://tex.z-dn.net/?f=%20%3D%2027%20%5Ctimes%20%20%5Cfrac%7B1%7D%7B27%7D%20)
![= 1](https://tex.z-dn.net/?f=%20%3D%201)
Step-by-step explanation:
Should be Emily, Morgan, Kali, Rosa
Since the vertex is at (-3, 6), the equation is given by
y = a(x + 3) + 6
Therefore, option A is the correct answer.